Advergames as Marketing Communication Media Opportunities - Alvian Alrasid Ajibulloh (Komuniti: Jurnal Komunikasi dan Teknologi Informasi, 2021)
The pandemic has had a major influence on consumer behavior trends, and it is considered that business actors need to make several adaptations so that the market does not abandon it. And in the process of selecting marketing media, media games can be used as an alternative at this time, because from some of the results of previous research on the combination of games and advertising, it can have a positive impact on marketing. Therefore, the researcher wants to investigate further about the opportunities that can be obtained from the use of media advergames to assist marketing communication activities in this pandemic situation, by using the literature study method from several previous scientific journals. The research results reveal that the media advergames are able to provide benefits in the marketing process such as being able to create experiential marketing, brand engagement, product placement.